2019
DOI: 10.1136/bcr-2019-229852
|View full text |Cite
|
Sign up to set email alerts
|

Arm malignant peripheral nerve sheath tumour: a rare clinical presentation

Abstract: Soft tissue sarcomas account for about 1% of malignant tumours. More than 50 subtypes of these tumours have been described with some being extremely rare, namely malignant peripheral nerve sheath tumours (MPNST). The authors present a case of a man aged 81 years with a medical history of an adenocarcinoma of the rectum, which was referred to our clinic due to a growing painless mass on the right arm. An MRI showed a well-delimited encapsulated mass involving the long head of the biceps muscle. Biopsy findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The included articles were published from 1993 to 2021 and were categorized as level 4 or 5 according to OCEBM. 4 5 6 7 8 9 10 11 12 13 14 15 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included articles were published from 1993 to 2021 and were categorized as level 4 or 5 according to OCEBM. 4 5 6 7 8 9 10 11 12 13 14 15 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43…”
Section: Resultsmentioning
confidence: 99%
“…Considering these criteria, the LD, vastus lateralis, gracilis, TFL, rectus femoris, and rectus abdominis are each considered appropriate donor muscles for FMT. In our systematic review, the LD was the most commonly used donor muscle, employed in more than half of reported cases to reconstruct defects in the anterior 10 33 35 41 43 and posterior 33 arm, deltoid, 7 34 shoulder, 4 7 and scapular region. 38 Terzis and Kostopoulos 46 reported that the LD achieved greater muscle power than did the rectus femoris and gracilis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation